A Reproduction of "Formal Designation of Brazilian Indigenous Lands Linked to Small but Consistent Reductions in Deforestation" - Darcy Ramos da Silva Neto; Joubert Ryan da Silva Cavalcante; Jhonatan Kallil Bernabé (Institute for Replication (I4R), 2024)
We reproduced West (2024) "Formal designation of Brazilian indigenous lands linked to small but consistent reductions in deforestation," which investigates the impact of formally recognizing Indigenous Lands (ILs) on deforestation rates in Brazil from 1986 to 2021. The original study uses a quasi-experimental design, employing temporal and sectional matching methods to compare deforestation rates before and after IL designation, concluding an average reduction of -0.05% in deforestation. To verify these findings, we conducted three main tests: a logit analysis, the consideration of negative deforestation values in the Atlantic Forest, and the synthetic control method. The logit analysis assessed the relationship between IL designation and covariates like land size, elevation, slope, and proximity to urban centers, confirming that these factors significantly influence IL designation, consistent with the original study. We also examined the treatment of negative deforestation values in the Atlantic Forest, originally treated as zero. By retaining these values, we found no significant impact on the study's overall results, indicating that the original methodological choice did not affect the main conclusions. Finally, the synthetic control method was used to replicate the counterfactual analysis of IL-designated areas, demonstrating that these areas consistently exhibited lower deforestation rates compared to the synthetic control post-2011. These tests confirmed the original study's findings, demonstrating that the formal designation of ILs contributes to small but significant reductions in deforestation, supporting the effectiveness of ILs as a strategy for environmental conservation and indigenous rights protection. The reproducibility of these results reinforces the study's conclusions.
Keywords: 330; Land tenure; Governance; Impact evaluation; Matching; Leakage